APPLICATION OF ROLE PLAY TECHNIQUE TO IMPROVE STUDENT’S SPEAKING SKILLS IN LEARNING ENGLISH - Salmita; Meristika Moetia (Nusantara Hasana Journal, 2023)
This study aims to improve the speaking skills of SMP N 1 Blangpidie students who are taught using role play learning techniques. This research uses quantitative methods and the type of research is classroom action research (CAR). Data collection techniques include questionnaires and student activity observation sheets. The application of this technique is carried out in 2 cycles. The stages of this research are: planning, action, observation and reflection stages. The results of this study indicate that there are results from the data based on cycle 1 58.65 to cycle 2 68.78. As for motivation, interest and self-confidence of students increased based on the result of the questionnaire interest 45,2 % who lacked interest 45,8 %and self-confidence 96,8 % while those who lacked confidence 3,2 %. It can be concluded that the use of role play techniques can improve students' speaking skills in learning English.